Leadership, Commitment, and Culture: A Meta-Analysis. (February 2013) - Jackson, Timothy A.; Meyer, John P.; Wang, Xiao-Hua (Frank)
The two purposes of this article were to examine the meta-analytic relationships between several well-studied forms of leadership and employee commitment and to test if some of these relationships vary due to societal culture. Transformational/charismatic leadership was shown to be positively related to affective (AC; ρ = .451, k = 116) and normative commitment (NC; ρ = .337, k = 30), while contingent reward and management-by-exception (active) were positively related to AC (ρ = .369, k = 51 and ρ = .083, k = 25, respectively). Laissez faire leadership was negatively related to AC (ρ = −.296, k = 15). In terms of culture, societal individualism-collectivism did not affect the relationship between transformational/charismatic leadership and AC. In contrast, the relationship between transformational/charismatic leadership and both NC and continuance commitment was stronger in countries that value collectivism. We also found evidence that the relationship between contingent reward and AC was stronger in societies with higher rather than lower levels of power distance/hierarchy. Implications of these findings on the study of leadership, culture, and commitment are discussed.